Targeting the Interleukin-5 Pathway for Treatment of Eosinophilic Conditions Other than Asthma - Roufosse, Florence (Frontiers in Medicine, 2018)
Improved understanding of the contribution of eosinophils to various chronic inflammatory conditions, most notably allergic asthma, has encouraged development of monoclonal antibodies specifically targeting mediators and surface receptors involved in eosinophil expansion and activation. The pivotal role of interleukin-5 (IL-5) in eosinophil biology, its high specificity for this leucocyte subset, and its involvement in the majority of eosinophilic conditions make it a very enticing target for treatment of eosinophil-mediated disorders. Two types of antibodies have been developed to target eosinophils: antibodies against IL-5 (mepolizumab and reslizumab), and an antibody against the IL-5-receptor-alpha-chain (IL-5Rα) (benralizumab). Both types of antibodies prevent IL-5 from engaging its receptor and in addition, anti-IL-5Rα antibodies induce target cell lysis. They have been shown to reduce circulating eosinophil counts rapidly in humans with various disorders. Herein, a brief overview of the role of IL-5 in eosinophil biology will be presented, followed by a description of the development and characteristics of antibodies targeting IL-5 or its receptor. Results of clinical trials evaluating the efficacy and safety of these new antibodies in diseases (other than eosinophilic asthma) with prominent tissue eosinophilia are reviewed, followed by safety considerations and potential future applications.